Embryonic development of Caspian kutum, Rutilus frisii kutum. - Jafari, Mahdieh; Kamarudin, Mohd Salleh; Saad, Che Roos; Arshad, Aziz; Oryan, Shahrbanoo; Tolouei Guilani, Mohamad Hossein (Wiley-Blackwell, 2010)
Rutilus frisii kutum is related to the Cyprinid family and an endemic fish of the Caspian Sea. This study was conducted to describe a complete embryonic development of kutum. Embryos were reared from zygote to larvae at 14–16 C. The embryonic period of this fish was divided into nine periods and 30 stages, from fertilization to hatching. Diagnostic structural characteristics were described for each stage. The main periods were zygote, cleavage, morula, blastula, gastrula, neurula, segmentation, pharyngula, and hatching. Hatching occurred at 8–9 d post-fertilization.